PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TULUNGAGUNG) - Melda Praditya Firdauzi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The human resources has an important role for organizations or companies. Therefore, anorganization needs to appreciate all of the aspects in an employee in order to create the humanresources that is qualified and has the best performances. This research aims to explain the effectof the work environment and the motivation on employee performance in Populastion and CivilRegristration Agency in the regency of Tulunagung. The type of this research is an explanatoryresearch. Furthermore, the data will be analyzed with the help of a software named SmartPLS3.0.Based on the results of compatibility test with outer model and inner model, it can be concluded thework environment (X1) as the independent variable has positive effect who is not significant ondependent variable which is employee performance (Y) with positive path coefficient (0,079), t-statisticfor 0,586 with p-value >0,05 (0,558). Meanwhile, the motivation variable (X2) has a positive effectthat significant on the employee performance with positive coefficient (0,736), t-statistic for7,723 with p-value <0,05.Keywords: Work Environment, motivation, and employee performance